Pediatric Uveitis in a Tertiary Referral Center in East China: Clinical Patterns and Visual Outcomes - Boya Lei; Xianjin Zhou; Ruiping Gu; Qinmeng Shu; Xinyi Ding; Rui Jiang; Qing Chang; Gezhi Xu; Haimei Liu; Li Sun; Min Zhou (Journal of Ophthalmology)
Conclusions: Pediatric uveitis was predominantly chronic and noninfectious, with anterior involvement. Systemic therapy was required by most patients, and most eyes showed improved visual acuity.